A Model for the Development of Mothers' Perceived Vulnerability of Preterm Infants. Issue 5 (June 2015) - Horwitz, Sarah McCue; Storfer-Isser, Amy; Kerker, Bonnie D.; Lilo, Emily; Leibovitz, Ann; St. John, Nick; Shaw, Richard J.
ABSTRACT: Objective: Some mothers of preterm infants continue to view them as vulnerable after their health has improved. These exaggerated perceptions of vulnerability lead to poor parent-child interactions and, subsequently, to adverse child outcomes. However, there is no theoretical model to explain why these exaggerated perceptions develop in only some mother-child dyads. Method: Data for this study come from a randomized trial of an intervention to reduce distress in mothers of preterm infants. A total of 105 mothers older than 18 years of infants aged 25–34 weeks, weighing >600 g and with clinically significant anxiety, depression, or trauma symptoms, were recruited and randomized. Women were assessed at baseline, after intervention, and at 6 months after birth. The outcome for these analyses was perceptions of infant vulnerability as measured by the Vulnerable Baby Scale (VBS) at 6 months after birth. A theoretical model developed from the extant literature was tested using the MacArthur Mediator-Moderator Approach. Results: A dysfunctional coping style, high depression, anxiety, or trauma symptoms in response to the preterm birth, and low social support were related to 6-month VBS scores. Maternal response to trauma was directly related to VBS, and an important precursor of maternal response to trauma was a dysfunctional coping style. Conclusions: This model suggests that maternal responses to trauma are critical in the formation of exaggerated perceptions of vulnerability as are dysfunctional coping styles and low social support. Women with these characteristics should be targeted for intervention to prevent poor parenting practices that result from exaggerated perceptions of vulnerability.